Nightly biting bycles of Anopheles species in rural Northwestern Burkina Faso - Dambach, Peter; Schleicher, Michael; Korir, Patricia; Becker, Norbert (Journal of medical entomology, 2018)
Abstract. The biting behavior of anophelines is an important determinant of malaria transmission. Understanding the local vector host-seeking behavior, its out